Prevalence of age-related macular degeneration in rural southern China: the Yangxi Eye Study. Issue 5 (28th August 2017) - Jin, Guangming; Ding, Xiaohu; Xiao, Wei; Xu, Xiao; Wang, Lanhua; Han, Xiaotong; Xiao, Ou; Liu, Ran; Wang, Wei; Yan, William; An, Lei; Zhao, Jialiang; et al.
Abstract : Purpose: To describe the prevalence of age-related macular degeneration (AMD) among older adults in rural southern mainland China. Methods: Eligible persons aged 50 years or over were identified by geographically defined cluster sampling from Yangxi County, Guangdong Province, China. Participants underwent a standardised interview and comprehensive eye examinations from August to November in 2014. Digital retinal photographs were graded for AMD lesions using the Clinical Classification of Age-Related Macular Degeneration developed by the Beckman Initiative for Macular Research Classification Committee. Age-standardised prevalence of AMD and AMD lesions was calculated using the 2010 world population data and compared with those of other populations. Results: Of 5825 subjects who participated (90.7% response rate), 4881 (83.8%) had fundus photographs gradable for AMD. Early, intermediate and late AMD were present in 2003 (41.0%), 879 (18.0%) and 42 (0.86%) participants. The age-standardised prevalence of early, intermediate and late AMD was 40.4% (95% CI 39.6% to 41.2%), 17.6% (95% CI 17.0% to 18.2%) and 0.79% (95% CI 0.65% to 0.95%), respectively. Total AMD was more prevalent in men than in women (62.8% vs 57.1%). Conclusions: AMD is an important public health concern for rural southern China, and the prevalence of AMD was higher in men than in women.